Influence of TNF Alpha on Testosterone Induced Cardiac Effects in Isolated Frog Heart Model - M. Shanthi FX, N.H. Shah, M.G. Tyagi, A.K. Raja, A.V. Babu, R. Kumar, (Journal of Phytology, 2009)
The effect of Tumor necrosis factor-alpha and testosterone was evaluated on the isolated Rana tigrina frog heart. The isolated frog heart (n= 10) were used for this study and the effect of drugs on myocardial contractility and heart rate was ascertained. Namely three drugs testosterone (4mg), bicalutamide (8mg) and TNF-alpha antagonist infliximab (0.4mg) were utilized for this study. Testosterone caused an increase in heart rate by 11.28% and decrease in myocardial contractility by 17.67%. Similarly bicalutamide caused a 20.11% decrease Heart rate and 41.17% decrease in myocardial contractility. To ascertain the role of TNF-alpha, infliximab was perfused through the heart and it potentiated the inhibitory effect of testosterone on the myocardial contractility and heart rate. The results of this study suggest the importance of TNF-alpha and testosterone hormone in cardiovascular pathophysiology.